IMPLEMENTASI CARA DISTRIBUSI OBAT YANG BAIK (CDOB) PADA STANDAR OPERASIONAL PROSEDUR (SOP) PENGIRIMAN DI PBF Y: PERSPEKTIF APOTEKER PENANGGUNG JAWAB - Santika, Putu Ria Madhuvidya; Lestari, Ni Putu Carina Srivinka; Ugrasena, Putu Yudha (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Drug distribution is an important stage in the pharmaceutical service system that plays a role in maintaining the quality, safety, and effectiveness of therapy to the hands of patients. Good Drug Distribution Practices (CDOB) are a reference in ensuring the quality of distribution, including in the preparation and implementation of Standard Operating Procedures (SOP) for delivery at Pharmaceutical Wholesalers (PBF). This study aims to evaluate the implementation of CDOB in the delivery SOP at PBF Enseval, with a focus on the role of the Responsible Pharmacist (RP). The study used a descriptive qualitative method with an evaluative approach through regulatory analysis and interviews. The results showed that most aspects of CDOB have been implemented, including the completeness of SOPs, documentation, training, and internal audits. However, there are still limitations in the involvement of RP at the SOP preparation stage, the real-time temperature monitoring for cold chain products is not optimal, and the Corrective and Preventive Action (CAPA) documentation is not fully digital. It is necessary to strengthen the role of RP, integrate temperature monitoring technology, and digitize documentation as an effort to improve the quality of drug distribution.